Rigid Cranial Fixation for Robot-Assisted Stereoelectroencephalography in Toddlers: Technical Considerations. Issue 6 (22nd August 2019) - Alexander, Hepzibha; Fayed, Islam; Oluigbo, Chima O
Abstract: BACKGROUND: Stereoelectroencephalography (sEEG) using depth electrodes has become a mainstay of pediatric epilepsy surgery. This technique relies on rigid cranial fixation using skull pins, which forms the basis for accurate stereotactic navigation. The use of cranial fixation pins poses the threat of traumatic skull injuries in young children because of inadequate cranial bone thickness. OBJECTIVE: To describe a rigid cranial fixation technique involving the integrated Gel Head Ring from the DORO QR3 multipurpose skull clamp set (Pro Med Instruments) with superimposed pin fixation in children below the age of 36 mo undergoing sEEG. METHODS: Patients were placed in the supine position and the head was fixed using a DORO skull clamp with 3 pediatric cranial pins. The head was supported on the integrated Gel Head Ring, and a pin pressure of 20 pounds was applied. The DORO skull clamp set was then attached to the ROSA neurosurgical robot support telescopic arm for stereotactic navigation. RESULTS: We present an illustrative series of 2 patients below the age of 3 yr with medically refractory epilepsy who underwent sEEG using our modified cranial fixation technique. Head position and reference registration were stable throughout the surgeries. Postoperative volumetric computed tomography scans of the head showed accurate placement of sEEG depth electrodes and did not reveal any fractures or epidural hematoma. No other complications related to cranial fixation were noted. CONCLUSION: Concurrent use of rigid and nonrigid cranial fixation using the DORO skull clamp set provides safe and effective cranial fixation in infants and toddlers undergoing sEEG.